2022
DOI: 10.1007/s00500-022-06778-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel depreciation approach in an uncertain environment: interval type-2 fuzzy sets in the maritime industry

Abstract: This study aims to propose a novel model for the determination of depreciation in an environment of uncertainty. In the study, amortization methods were modified through interval type-2 fuzzy, and a new approach was proposed to help investors make decisions in an environment of cash flow uncertainty. We provide options among different depreciation alternatives for the future investment decisions of maritime companies through the revision of the straight-line depreciation method and the double-declining balance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 74 publications
(103 reference statements)
0
1
0
Order By: Relevance
“…Although crisp depreciation methods have been frequently studied by researchers, only two fuzzy depreciation studies have been found in the literature, to the best knowledge of the authors. Akan and Kiraci (2023) developed a novel interval type-2 fuzzy depreciation approach and applied in maritime industry. Khalili et al (2014) rewritten some classic methods for calculating depreciation in fuzzy form by using extension principle and α-cut technique.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although crisp depreciation methods have been frequently studied by researchers, only two fuzzy depreciation studies have been found in the literature, to the best knowledge of the authors. Akan and Kiraci (2023) developed a novel interval type-2 fuzzy depreciation approach and applied in maritime industry. Khalili et al (2014) rewritten some classic methods for calculating depreciation in fuzzy form by using extension principle and α-cut technique.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It includes 15 peer-reviewed articles on various aspects of summability techniques, applications of various summability techniques in solving a variety of problems, and also topics that are either already influenced by advanced summability techniques or appear to have enough scope for applying new and advanced summability techniques. In the following sections, we highlight some of the major aspects of the articles (Ibrahim 2020;Ahmad and Peters 2020;Malhotra and Gupta 2020;Akbar et al 2020;Sezer 2020;Akan and Kiraci 2022;Akram et al 2022;Sindhu and Rashid 2022;Belhadj and Bouanani 2022;Khaleghi and Eydi 2022;Khemiri et al 2022;Patro et al 2022;Kong and Wu 2022;Mehidi et al 2022; Andrade and Re ˆgo 2022) included.…”
mentioning
confidence: 99%